(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In this article, the role and function of "you-sen" and "you-siz" in the expression of politeness and impoliteness in English and Uzbek family discourse is analyzed on the basis of examples.